Theoretical Judgments about Legal Responsibility the State before the Individual: Array - Moraru, Elena; Robea, Mariana (Journal of Danubian Studies and Research, 2021)
The content of legal responsibility is a special kind of legal relationship between the state and a specific person. These relations are objective and universal in nature and their distinguishing feature is the ability to make mutual demands, this issue was considered by scientists, from Aristotle to Kant.